Silicon carbon material, preparation method thereof and lithium ion battery

By introducing transition metal carbon nanotube catalysts into porous carbon-loaded silicon matrix, carbon nanotubes are grown in situ and silicon nanoparticles or wires are formed, and finally carbon coating is carried out, which solves the problems of excessive expansion of silicon carbon materials and insufficient compressive strength in lithium-ion batteries, and achieves both conductivity and performance improvement.

CN119674014APending Publication Date: 2025-03-21SHANGHAI SHANSHAN TECH CO LTD
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202411875576.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing silicon carbon materials have problems such as excessive expansion, insufficient compressive strength, insufficient conductivity and high cost in lithium-ion batteries, making it difficult to achieve mass production.

Method used

By introducing a transition metal carbon nanotube catalyst into a porous carbon-supported silicon matrix, carbon nanotubes are grown in situ, and silicon nanoparticles and/or silicon nanowires are formed in situ in the carbon nanotube, and finally carbon coating is performed to prepare silicon carbon materials with excellent expansion inhibition and compressive strength.

Benefits of technology

The conductivity of silicon-carbon materials has been improved, taking into account capacity performance, rate performance and cycle performance, reducing production costs and improving the material's pressure resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674014A_ABST
    Figure CN119674014A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon carbon material, a preparation method thereof and a lithium ion battery. The preparation method of the silicon-carbon material comprises the following steps: S1, adding an alkaline reagent into a mixed solution containing a porous carbon-loaded silicon substrate, transition metal salt and a solvent, and drying to obtain a first precursor; s2, performing carbon deposition on the first precursor by adopting a chemical vapor deposition method, performing in-situ growth of a carbon nanotube, and then performing acid pickling and drying to obtain a second precursor; s3, performing silicon deposition on the second precursor by adopting a chemical vapor deposition method, and forming silicon nanoparticles and / or silicon nanowires in the carbon nanotubes in situ to obtain a third precursor; and S4, carrying out carbon coating on the third precursor to obtain the silicon carbon material. The silicon-carbon material is excellent in expansion inhibition performance and compressive strength and has excellent conductivity, and the lithium ion battery containing the silicon-carbon material can give consideration to excellent capacity performance, rate performance and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon-carbon material and a preparation method thereof and a lithium ion battery. Background Art

[0002] Silicon-carbon negative electrode materials are widely used due to their extremely high gram capacity. In order to alleviate the electrical contact failure caused by excessive expansion of silicon active materials, technicians in this field have developed silicon-carbon materials with a core-shell structure, that is, silicon as the core and a carbon shell coated on the outside. However, although the core-shell structure can greatly alleviate expansion, it has remained in the field of scientific research and is difficult to mass produce due to many problems such as difficulty in mass production, low rate, high cost, and difficulty in quality control. Later, improvements were made based on the core-shell structure until it was found that silicon nanoparticles were deposited inside the porous carbon by vapor deposition, and then a passivated carbon layer was wrapped, which made it possible to achieve mass production.

[0003] However, there are still many problems based on the current method of silicon deposition in porous carbon. First, the expansion of silicon is extremely large, and it is necessary to regulate the enlargement of pore volume and the consistency of voids. This step is limited by the preparation of the precursor and the carbon activation process, and it is extremely difficult to control, which undoubtedly greatly increases the cost of silicon-carbon negative electrode. Secondly, based on the previous deposition coating form, it is difficult to grow a thicker carbon shell on the surface of the material. It is generally believed that the shell wall structure can achieve the highest strength with the smallest mass, and it is difficult to completely fill the porous carbon with silicon in the structure obtained by silicon deposition in porous carbon. Therefore, it causes certain strength and elastic defects, and it is difficult to play a sufficient supporting role to improve the pressure resistance of silicon-carbon materials. In addition, the thin passivation layer is difficult to achieve sufficient passivation, which easily leads to the contact between the silicon-carbon negative electrode and the electrolyte in repeated expansion cycles, resulting in low-voltage gas production. Therefore, how to effectively inhibit the expansion of silicon and enhance the strength of silicon-carbon materials has always been a difficult problem in the industry. Summary of the invention

[0004] In order to solve the above problems existing in the existing silicon-carbon materials, the present invention provides a silicon-carbon material and a preparation method thereof and a lithium-ion battery. The silicon-carbon material has excellent expansion inhibition performance and compressive strength, and has excellent conductivity, and the lithium-ion battery containing the silicon-carbon material can take into account excellent capacity performance, rate performance and cycle performance.

[0005] In order to achieve the above technical objectives, the present invention adopts the following technical solutions.

[0006] The present invention provides a method for preparing a silicon-carbon material, which comprises the following steps:

[0007] S1, adding an alkaline reagent to a mixed solution containing a porous carbon-supported silicon substrate, a transition metal salt and a solvent, and drying to obtain a first precursor;

[0008] S2, performing carbon deposition on the first precursor by chemical vapor deposition to in-situ grow carbon nanotubes, and then acid-washing and drying to obtain a second precursor;

[0009] S3, using chemical vapor deposition to deposit silicon on the second precursor, forming silicon nanoparticles and / or silicon nanowires in situ in the carbon nanotubes, to obtain a third precursor; wherein the gas source of the second chemical vapor deposition includes a silicon source;

[0010] S4. Carbon-coating the third precursor to obtain the silicon-carbon material.

[0011] In the present invention, in step S1, the transition metal salt reacts with an alkaline reagent to generate nano transition metal oxides. During the reaction, the nano transition metal oxides are generated preferentially in the mesopores and macropores of the porous carbon-supported silicon matrix, and then on the surface.

[0012] In the present invention, the transition metal salt may be a soluble salt of a transition metal conventional in the art that can catalyze the growth of carbon nanotubes in the form of an oxide or a single substance.

[0013] In step S1, the transition metal salt preferably includes one or more of iron salt, nickel salt and cobalt salt.

[0014] In step S1, the transition metal salt may include a divalent salt and / or a trivalent salt of a transition metal.

[0015] In some preferred embodiments, in step S1, the transition metal salt includes a divalent salt and a trivalent salt of iron; wherein the molar ratio of the divalent salt to the trivalent salt of iron is preferably (2-4):1.

[0016] In step S1, the transition metal salt preferably includes one or more of transition metal hydrochlorides, transition metal nitrates, transition metal sulfates, transition metal acetates and transition metal citrates.

[0017] In some specific embodiments, the transition metal salt comprises ferrous sulfate and ferric chloride, wherein the molar ratio of ferrous sulfate to ferric chloride is preferably (2-4):1.

[0018] In some specific embodiments, the transition metal salt includes cobaltous sulfate and cobalt chloride, wherein the molar ratio of cobaltous sulfate to cobalt chloride is preferably (2-4):1.

[0019] In some embodiments, the transition metal salt comprises ferric chloride.

[0020] In some embodiments, the transition metal salt comprises ferric nitrate.

[0021] In some embodiments, the transition metal salt comprises cobalt nitrate.

[0022] In step S1, the content of the transition metal salt is preferably 0.01-0.3 mol / kg, for example 0.02 mol / kg, and the content is the molar number of the transition metal element in the transition metal salt relative to 1 kg of the porous carbon-supported silicon substrate.

[0023] In step S1, the alkaline reagent may include a weak alkaline reagent and / or a strong alkaline reagent, preferably ammonia water.

[0024] The concentration of the ammonia water is preferably 1-10%, such as 5%, where the percentage is the mass of ammonia to the total mass of the ammonia water.

[0025] In step S1, the mass ratio of the alkaline reagent to the solvent is preferably (1-10):100.

[0026] In step S1, the mixed solution preferably also includes a complexing agent. Based on the complexing effect of the complexing agent, the nano-size and uniformity of the transition metal oxide in the reaction can be greatly promoted, and its agglomeration phenomenon can be further alleviated. In addition, when the complexing agent is added, the complexing agent is coated on the surface of the porous carbon-loaded silicon substrate, and some oxygen-containing groups will be retained after carbonization, and the hydrogen bonds and van der Waals forces between the complexing agent and the polar binder are stronger, and thus the bonding effect is stronger, which can inhibit powder loss; when the complexing agent contains metal atoms, it is easy to change the smoothness of the subsequent coated carbon layer after carbonization, increase the contact degree between the subsequent coated carbon layer and the surface of the porous carbon-loaded silicon substrate, and is more conducive to the improvement of the strength of the subsequent coated carbon layer; and the doping of metal atoms in the coated carbon layer has the effect of transforming the carbon material into amorphous carbon, changing the disordered structure of the amorphous carbon material, and effectively inhibiting the buffer stress and expansion of the surface of the silicon-carbon material, and improving the pressure resistance of the silicon-carbon material.

[0027] The complexing agent may include an organic acid and / or an organic acid salt, preferably one or more of acetic acid, citric acid, EDTA and salts thereof, for example, one or more of ferric acetate, sodium acetate, ferric citrate, sodium citrate and EDTA.

[0028] Wherein, the mass ratio of the complexing agent to the porous carbon-supported silicon substrate is preferably 1:(5-1000), for example 1:10.

[0029] In step S1, the solvent is preferably deionized water.

[0030] In step S1, the mass ratio of the porous carbon-supported silicon substrate to the solvent is preferably 1:(5-50), for example 1:10.

[0031] In step S1, the adding is preferably performed under stirring conditions.

[0032] Wherein, the stirring speed is preferably 100-1000r / min, for example 300r / min.

[0033] In step S1, the alkaline reagent is preferably added dropwise, and the alkaline reagent is added at a rate of 5-50 mL / min, such as 10 mL / min.

[0034] In step S1, the operation of adding the alkaline reagent is preferably performed under a protective atmosphere. The protective atmosphere preferably includes one or more of an inert atmosphere, a reducing atmosphere and a carbon dioxide atmosphere, for example, one or more of nitrogen, argon, helium, hydrogen and carbon monoxide.

[0035] In step S1, the method for preparing the mixed solution may include: immersing the porous carbon-supported silicon substrate in a solvent, and then adding a transition metal salt to obtain a mixed solution.

[0036] In step S1, the drying can be performed by conventional methods in the art, preferably spray drying.

[0037] In step S1, the drying speed may be 0.5-3 kg / h, for example, 1 kg / h.

[0038] In step S1, the drying temperature is preferably 150-300°C, for example 200°C.

[0039] In step S1, the drying may be performed under a protective atmosphere, such as nitrogen.

[0040] In step S1, the Dv50 particle size of the first precursor may be 1-10 μm, for example, 8 μm.

[0041] In step S1, after adding the alkaline reagent and before drying, an alcoholization step is preferably further included. The alcoholization step can further increase the degree of reaction of the transition metal salt to form the transition metal oxide. The alcoholization temperature is preferably 80-100° C., such as 90° C.; the alcoholization time is preferably 1-10 h, such as 5 h.

[0042] In the present invention, in step S2, the transition metal oxide in the first precursor and / or the transition metal element obtained after reduction can catalyze the in-situ growth of carbon nanotubes. While the carbon nanotubes are grown in-situ, the carbon coating process is carried out simultaneously. At this time, the grown carbon nanotubes can grow in the form of embedded carbon layers, and after protruding out of the carbon layer, it is helpful to carbon coat again, speed up the coating speed, and thicken the carbon layer. Among them, when the carbon nanotubes are grown in-situ, whether the carbon nanotubes are single-walled carbon nanotubes or multi-walled carbon nanotubes depends on the loading amount of the transition metal, the uniformity of distribution, and the nano-degree of the transition metal oxide.

[0043] In step S2, the carbon nanotubes may include single-walled carbon nanotubes and / or multi-walled carbon nanotubes, wherein the pore size of the multi-walled carbon nanotubes is preferably 5-50 nm, and the pore size of the single-walled carbon nanotubes is preferably 2-20 nm.

[0044] In step S2, before the carbon deposition, a step of reducing the first precursor may be further included.

[0045] The reduction temperature is preferably 400-800°C, such as 550°C.

[0046] The reduction is preferably carried out in a reducing atmosphere; the reducing atmosphere is preferably hydrogen; the ventilation volume of the reducing atmosphere is preferably 0.1-10 L·kg -1 ·min -1 , for example 1L kg -1 ·min -1 .

[0047] The reduction time is preferably 30-300 min, for example 120 min.

[0048] In step S2, the carbon deposition may adopt a carbon source conventionally used for vapor deposition in the art, preferably including one or more of alkynes, alkanes, olefins, aromatic compounds and carbohydrates, such as acetylene.

[0049] In step S2, during the carbon deposition process, the ventilation rate of the carbon source is preferably 2-10 L·kg -1 ·min -1 .

[0050] In step S2, the carbon deposition time is preferably 5-120 min, for example 15 min.

[0051] In step S2, the temperature of the carbon deposition is preferably 500-700°C, such as 550°C.

[0052] In step S2, the pickling preferably includes a step of washing with hydrochloric acid; the mass ratio of the hydrochloric acid to the product obtained by the carbon deposition is (5-50):1, for example 10:1; the concentration of the hydrochloric acid may be 1-6 mol / L.

[0053] In step S2, the drying can be performed in a conventional manner in the art, preferably spray drying or vacuum drying.

[0054] In the present invention, in step S2, the acid washing treatment after the carbon deposition is beneficial to remove the transition metal and open the opening of the carbon nanotubes, so that the silicon source can be preferentially deposited in the carbon nanotubes during the subsequent silicon deposition through adsorption.

[0055] In step S2, the Dv50 particle size of the second precursor is preferably 4-20 μm, such as 8 μm.

[0056] In the present invention, in step S3, when the silicon is deposited, silicon nanowires are formed in situ in the multi-walled carbon nanotubes, and silicon nanoparticles are formed in situ in the single-walled carbon nanotubes. By depositing silicon nanowires in multi-walled carbon nanotubes, it is possible to sacrifice toughness in exchange for maximum strength and support, and to play the role of the main beam and foundation, and to sacrifice a certain gram capacity, to maximize the reduction of expansion, and to achieve an increase in volume energy density. By depositing silicon nanoparticles in single-walled carbon nanotubes, the toughness of carbon nanotubes and the strength increased by filling with silicon nanoparticles are taken into account. On the premise of increasing the gram capacity, the expansion is reduced and the compressive strength is improved.

[0057] In step S3, the temperature of silicon deposition is preferably 400-800°C, for example 500°C.

[0058] In step S3, the silicon deposition is preferably performed at a pressure of 0.1-2 MPa, for example, at 0.2 MPa.

[0059] In step S3, the silicon deposition time is preferably 5-60 min, for example, 20 min.

[0060] In step S3, the silicon source may include silane, and the silane preferably includes one or more of monosilane, disilane, trisilane and butasilane.

[0061] In step S3, the ventilation volume of the silicon source is preferably 0.01-1 L·kg -1 min -1 , for example 0.5 L·kg - 1 min -1 .

[0062] In step S3, preferably, the gas source for silicon deposition also includes a carrier gas; wherein the volume ratio of the silicon source to the carrier gas is 1:(2-6), for example, 1:4.

[0063] In step S3, the gas source for silicon deposition preferably further includes a doping element gas, and the doping element gas preferably includes one or more of a Group III element compound gas and a Group V element compound gas, such as one or more of carborane, gallium nitrate, phosphine and arsine. Preferably, the amount of the doping element gas introduced is 0.01-0.5 L·kg -1 min -1 .

[0064] In the present invention, in step S4, the carbon coating may include the following steps: performing carbon deposition on the third precursor by using chemical vapor deposition.

[0065] The carbon source of the carbon deposition preferably includes one or more of alkynes, alkanes, olefins, aromatic compounds and carbohydrates, such as acetylene.

[0066] In the process of carbon deposition, the ventilation volume of the carbon source is preferably 0.1-10 L·kg -1 ·min -1 , for example 2L·kg -1 ·min -1 .

[0067] The carbon deposition time is preferably 300-600 min, such as 480 min.

[0068] The carbon deposition temperature is preferably 400-800°C, such as 550°C.

[0069] Porous carbon supported silicon substrate

[0070] In the present invention, the porous carbon-supported silicon substrate can be conventional in the art, generally comprising porous carbon and silicon, wherein the silicon is distributed in the pores and / or on the surface of the porous carbon; the porous carbon-supported silicon substrate comprises mesopores and macropores. The porous carbon-supported silicon substrate of the present invention can be prepared by conventional methods in the art.

[0071] In some embodiments, in step S1, the porous carbon-supported silicon substrate satisfies one or more of the following conditions ①-⑥:

[0072] ① The silicon content of the porous carbon-supported silicon substrate is 30%-70%, for example, 50%, where the percentage is mass percentage;

[0073] ② The carbon content of the porous carbon-supported silicon substrate is 30%-70%, for example, 50%, where the percentage is mass percentage;

[0074] ③ The specific surface area of ​​the porous carbon-supported silicon substrate is 0.5-5 m 2 / g, for example, 3.4m 2 / g;

[0075] ④ The Dv50 particle size of the porous carbon-supported silicon substrate is 4-20 μm, for example, 8.0 μm;

[0076] ⑤ The 1MPa powder resistivity of the porous carbon-supported silicon substrate is 0.01-20 Ω·cm, for example, 9.6 Ω·cm;

[0077] ⑥ The ID / IG of the porous carbon-supported silicon substrate is 0.1-1.4, for example, 0.9.

[0078] In some embodiments, the method for preparing the porous carbon-supported silicon substrate comprises: depositing silicon on porous carbon using a chemical vapor method to obtain the porous carbon-supported silicon substrate.

[0079] The gas source for silicon deposition includes a silicon source, and the silicon source may include silane. The silane preferably includes one or more of monosilane, disilane, trisilane and butadienesilane.

[0080] The gas source for silicon deposition preferably includes a silicon source and a carrier gas, and the volume ratio of the silicon source to the carrier gas is preferably 1:(2-6), for example, 1:4.

[0081] The silicon deposition temperature is preferably 400-800°C, for example 500°C.

[0082] The silicon deposition time may be 1-20 hours, for example, 10 hours.

[0083] Preferably, the step of coating a passivation layer is further included after the silicon deposition; the passivation layer preferably includes a carbon layer and / or an oxide layer.

[0084] In some specific embodiments, the carbon layer is obtained by carbon deposition using a chemical vapor deposition method.

[0085] Wherein, the gas source for carbon deposition includes a carbon source, and the carbon source preferably includes one or more of alkynes, alkanes, alkenes, aromatic compounds and carbohydrates, such as acetylene. Preferably, the gas source for carbon deposition includes a carbon source and a protective gas, and the protective gas preferably includes one or more of nitrogen, helium and argon.

[0086] In the process of carbon deposition, the ventilation volume of the carbon source is preferably 0.1-10 L·kg -1 ·min -1 , for example 5L·kg-1 ·min -1 .

[0087] Wherein, the carbon deposition time is preferably 2-20 hours.

[0088] The carbon deposition temperature is preferably 400-800°C, such as 500°C.

[0089] In the present invention, the porous carbon may be conventional porous carbon in the art.

[0090] In some embodiments, the porous carbon satisfies one or more of the following conditions: ① The specific surface area is 1200-3000m 2 / g, ② micropore volume accounts for 60-100%, ③ mesopore and above pore volume accounts for 0-40%, ④ pore volume is 0.7-1.5 cm 3 / g.

[0091] In some specific embodiments, the porous carbon satisfies one or more of the following conditions: ① The specific surface area is 1890 m 2 / g, ② micropore volume accounts for 85.3%, ③ mesopore and above pore volume accounts for 14.7%, ④ pore volume is 1.32cm 3 / g.

[0092] In the present invention, the porous carbon can be prepared by conventional methods in the art. The carbon source of the porous carbon can include one or more of resin, sucrose, glucose, fructose, starch, cellulose, triglyceride, fatty acid, hemicellulose, lignin and asphalt, preferably resin, more preferably phenolic resin.

[0093] In some embodiments, the porous carbon in the porous carbon-supported silicon matrix is ​​prepared using phenolic resin as a carbon source.

[0094] In some specific embodiments, the method for preparing porous carbon comprises the following steps:

[0095] (1) spray drying a slurry containing a phenolic resin to obtain a carbon material precursor;

[0096] (2) carbonizing the carbon material precursor to obtain a porous carbon precursor;

[0097] (3) Activating the porous carbon precursor to obtain porous carbon.

[0098] In step (1), the slurry may further include a curing agent and a solvent; the curing agent is, for example, hexamethylenetetramine, and the solvent is, for example, ethanol. The mass ratio of the phenolic resin to the curing agent is preferably 100:(1-20), for example, 100:6.

[0099] In step (1), the spray drying temperature is preferably 90-180°C, for example 130°C.

[0100] In step (1), the spray drying is preferably performed to a particle diameter of 4-20 μm, for example, 8 μm.

[0101] In step (2), the carbonization method may be a conventional carbonization method in the art, such as a staged heat treatment; preferably, the carbonization includes the following stages:

[0102] The first stage: heat up to 150-250℃ at 1-10℃ / min, keep warm for 50-180 min;

[0103] The second stage: heat up to 600-700℃ at 1-10℃ / min and keep warm for 50-180 min.

[0104] In some specific embodiments, the carbonization comprises the following stages:

[0105] The first stage: heating to 200℃ at a heating rate of 4℃ / min and keeping the temperature for 60min;

[0106] The second stage: heat up to 652°C at a heating rate of 4°C / min and keep warm for 60 minutes.

[0107] In step (2), the carbonization can be carried out under an inert atmosphere, and the inert atmosphere preferably includes one or more of nitrogen, helium and argon.

[0108] In step (3), the activation method can be a conventional activation pore-forming method in the art, such as alkali activation or gas activation, preferably gas activation.

[0109] Wherein, the gas activation is preferably carbon dioxide activation or water vapor activation.

[0110] The ventilation volume of the gas activation is preferably 10-50 L·kg -1 ·min -1 , for example 2·L·kg -1 ·min -1 .

[0111] The gas activation temperature is preferably 450-800°C, for example 550°C.

[0112] The gas activation time is preferably 5-15 h, for example 9 h.

[0113] The present invention provides a silicon-carbon material, which is prepared by the method for preparing the silicon-carbon material as described above.

[0114] The present invention provides a silicon-carbon material, which includes a core-shell structure, wherein the core-shell structure includes an inner core and an outer shell covering the inner core, wherein the inner core includes a porous carbon-loaded silicon matrix, and along a direction away from the inner core, the outer shell includes a first carbon layer and a second carbon layer in sequence, wherein carbon nanotubes are distributed in at least one of the porous carbon-loaded silicon matrix, the first carbon layer and the second carbon layer, and silicon nanoparticles and / or silicon nanowires are distributed in at least some of the carbon nanotubes.

[0115] In some preferred embodiments, the distribution of the carbon nanotubes includes one or more of the following modes ①-⑤:

[0116] ① The carbon nanotubes are distributed inside the porous carbon-supported silicon substrate;

[0117] ② The carbon nanotubes extend from the interior of the porous carbon-loaded silicon substrate and sequentially penetrate the first carbon layer and the second carbon layer;

[0118] ③ The carbon nanotubes extend from the interior of the porous carbon-loaded silicon substrate and penetrate the first carbon layer and are embedded in the second carbon layer;

[0119] ④ The carbon nanotubes extend from the inside of the first carbon layer and penetrate the second carbon layer;

[0120] ⑤ The carbon nanotubes extend from the inside of the first carbon layer and are embedded in the second carbon layer.

[0121] In some preferred embodiments, the shell further comprises a silicon layer, wherein the silicon layer is located between the first carbon layer and the second carbon layer.

[0122] In some preferred embodiments, the silicon nanoparticles and / or silicon nanowires further include doping elements.

[0123] The doping element preferably includes one or more of the third main group elements and the fifth main group elements, for example, one or more of nitrogen, boron, gallium, phosphorus and arsenic.

[0124] The content of the doping element is preferably 0.05%-0.2%, for example 0.1%, where the percentage is the mass percentage of the silicon-carbon material.

[0125] In the present invention, the carbon content of the silicon-carbon material may be 20%-80%, preferably 50%-60%, for example, 50.5%, 50.9%, 51.6%, 52.1%, 52.2%, 52.3%, 52.4%, 52.9%, 53.1%, 53.4%, 54.7%, 54.9% or 56.2%, where the percentage is the mass percentage of the silicon-carbon material.

[0126] In the present invention, the silicon content of the silicon-carbon material may be 20%-60%, preferably 40%-50%, for example, 43.8%, 45.1%, 45.2%, 45.3%, 46.5%, 46.9%, 47.1%, 47.5%, 47.6%, 47.8%, 47.9%, 48.4%, 49.1% or 49.5%, where the percentage is the mass percentage of the silicon-carbon material.

[0127] In the present invention, the iron content of the silicon-carbon material may be 0.05%-0.1%, where the percentage is the mass percentage of the silicon-carbon material.

[0128] In the present invention, the nickel content of the silicon-carbon material may be 0.05%-0.1%, where the percentage is the mass percentage of the silicon-carbon material.

[0129] In the present invention, the cobalt content of the silicon-carbon material may be 0.05%-0.1%, where the percentage is the mass percentage of the silicon-carbon material.

[0130] In the present invention, the 1 MPa powder resistivity of the silicon-carbon material may be 0.01-20 Ω·cm, preferably 1-15 Ω·cm, for example, 1.5 Ω·cm, 1.6 Ω·cm, 2.0 Ω·cm, 2.1 Ω·cm, 2.4 Ω·cm, 3.1 Ω·cm, 3.5 Ω·cm, 3.9 Ω·cm, 4.2 Ω·cm, 4.3 Ω·cm, 4.7 Ω·cm, 4.9 Ω·cm, 5.2 Ω·cm, 5.3 Ω·cm, 6.7 Ω·cm, 6.5 Ω·cm, 7.3 Ω·cm, 7.8 Ω·cm, 9.1 Ω·cm, 10.4 Ω·cm or 13.2 Ω·cm.

[0131] In the present invention, the single particle strength of the silicon-carbon material can be 5-30 MPa, for example, 8.8 MPa, 11.5 MPa, 11.8 MPa, 12.4 MPa, 13.4 MPa, 15.3 MPa, 16.1 MPa, 18.7 MPa, 19.5 MPa, 19.8 MPa, 20.1 MPa, 20.2 MPa, 20.3 MPa, 20.5 MPa, 20.6 MPa, 21.5 MPa, 23.1 MPa, 25.7 MPa, and 26.2 MPa.

[0132] In the present invention, the specific surface area of ​​the silicon-carbon material may be 1-2 m 2 / g, for example, 1.1 m 2 / g, 1.4 m 2 / g, 1.3 m 2 / g, 1.2 m 2 / g, 1.5 m 2 / g, 1.6 m 2 / g or 1.9 m 2 / g.

[0133] In the present invention, the Dv50 particle size of the silicon-carbon material may be 5-10 μm, preferably 8-9.5 μm, for example, 8.1 μm, 8.2 μm, 8.3 μm, 8.4 μm, 8.5 μm, 8.6 μm, 8.7 μm or 9.1 μm.

[0134] In the present invention, the silicon-carbon material satisfying the above-mentioned structure, composition and performance parameters can be prepared by the aforementioned method for preparing the silicon-carbon material.

[0135] The present invention also provides a pole piece, which comprises the silicon-carbon material as described above.

[0136] The present invention provides an application of the silicon-carbon material as described above as a negative electrode material in a lithium-ion battery.

[0137] The present invention also provides a lithium ion battery, which comprises the silicon-carbon material as described above.

[0138] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0139] The reagents and raw materials used in the present invention are commercially available.

[0140] The positive and progressive effects of the present invention are:

[0141] The present invention introduces a transition metal carbon nanotube catalyst into a porous carbon-supported silicon matrix by a liquid phase reaction method, grows carbon nanotubes in situ, forms silicon nanoparticles and / or silicon nanowires in situ in the carbon nanotubes during subsequent silicon deposition, and finally performs a layer of carbon coating. The obtained silicon-carbon material can achieve a balance of strength, toughness, conductivity and capacity on the one hand, and on the other hand, by depositing silicon-carbon composite materials on the surface and / or in the pores of the porous carbon, the direct contact force between the coating layer and the porous carbon is effectively increased, thereby suppressing cycle failure. The lithium ion battery using the silicon-carbon material of the present invention can achieve excellent capacity performance, rate performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0142] Figure 1 This is a schematic structural diagram of the silicon-carbon material obtained when multi-walled carbon nanotubes are grown in situ and silicon nanowires are formed in situ after silicon is deposited in an embodiment.

[0143] Figure 2 This is a schematic structural diagram of the silicon-carbon material obtained when single-walled carbon nanotubes are grown in situ and silicon nanoparticles are formed in situ after silicon is deposited in the embodiment.

[0144] Reference numerals:

[0145] Silicon Nanoparticles 1

[0146] Silicon Nanowire 2

[0147] Carbon Nanotubes 5

[0148] Porous carbon supported on silicon matrix Porous carbon 3

[0149] Silicon particles in porous carbon-supported silicon matrix 4

[0150] First carbon layer 6

[0151] Second carbon layer 7 DETAILED DESCRIPTION

[0152] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0153] In the following examples and comparative examples, the phenolic resin was purchased from Hubei Hengye Technology Co., Ltd., model 2135.

[0154] In the following examples and comparative examples, the preparation of the porous carbon-supported silicon substrate includes the following steps (the total steps are denoted as S0):

[0155] (1) Precursor preparation: 1 kg of phenolic resin, 2 kg of ethanol and 60 g of hexamethylenetetramine (HMT) were mixed using a high-speed homogenizer at a speed of 2000 r / min for 60 min. The mixture was spray dried at 130 °C until the Dv50 particle size was 8 μm, thereby obtaining a carbon material precursor.

[0156] (2) Carbonization: The carbon material precursor is placed in a rotary furnace for cross-linking at 10r / min, and then carbonized. The heating curve in the first stage is 4℃ / min, and the temperature is raised to 200℃ and kept for 1h. The main purpose is to make the phenolic resin cross-linked. The heating curve in the second stage is 4℃ / min, and the temperature is raised to 652℃ and kept for 1h. The ventilation volume of the nitrogen atmosphere is 1 L·kg -1 min -1 , a porous carbon precursor is obtained;

[0157] (3) Activation: The porous carbon precursor was activated in a CO2 atmosphere for 9 h to obtain porous carbon with a ventilation volume of 2 L kg - 1 min -1 The furnace temperature was adjusted to 550°C, and the specific surface area was 1890m 2 / g and micropore volume accounts for 85.3%, mesopore volume accounts for 14.7%, and pore volume is 1.32cm3 / g.

[0158] (4) Silane deposition: The atmosphere was switched to a silane mixture (20% silane and 80% argon by mass), and the nuclei were formed by deposition at 500 °C for 10 h with a ventilation volume of 15 L kg -1 min -1 .

[0159] (5) Passivation layer coating: The atmosphere is then switched to acetylene with a ventilation volume of 2 L kg -1 min -1 , continue to deposit at 500°C for 2h, then switch to nitrogen, and then cool to room temperature 25°C to obtain a porous carbon-loaded silicon substrate.

[0160] The porous carbon-supported silicon matrix has a silicon content of 50%, a carbon content of 50%, and a specific surface area of ​​3.4 m 2 / g, D50=8.0, 1MPa powder resistivity is 9.6 Ω·cm, ID / IG is 0.9.

[0161] Example 1

[0162] S1. Preparation of the first precursor:

[0163] (1) 1 kg of the porous carbon-supported silicon substrate prepared in step S0 was immersed in 10 kg of deionized water, and 100 g of sodium citrate, a complexing agent, was added, and then 0.0133 mol of ferrous sulfate was added, with the molar ratio of ferrous sulfate to ferric chloride being 2:1, and ferric chloride was added; then 1 kg of 5% ammonia water was added at a dropping rate of 10 mL / min; after the addition was completed, the mixture was alcoholized at 90°C for 5 h.

[0164] The above adding steps all require stirring at a speed of 300 r / min, and inert gas (nitrogen) is used for protection throughout the process.

[0165] (2) Drying and granulation: spray drying is performed under nitrogen atmosphere protection at a drying rate of 1 kg / h at 200°C to obtain a first precursor with a Dv50 particle size of 8 μm.

[0166] S2. Preparation of the second precursor:

[0167] (1) Hydrogen reduction: At a temperature of 550°C and a ventilation volume of 1 L kg -1 min -1 Under the above conditions, the first precursor was reduced by ventilation for 120 min.

[0168] (2) Carbon deposition: The product obtained in step (1) was subjected to chemical vapor deposition in an acetylene atmosphere, wherein the acetylene flow rate was 2 L·kg-1 min -1 , time is 120min, temperature is 550℃.

[0169] (3) Pickling: Pickling is performed several times with 1 mol / L hydrochloric acid. The mass ratio of hydrochloric acid to the product obtained by carbon deposition in step (2) is 10:1 in each pickling. Pickling is performed until no transition metal is present on the surface of the material and the magnetic foreign matter impurities are below 10 ppm.

[0170] (4) Drying: The acid-washed product was mixed with 10 times the mass of deionized water and then spray-dried to obtain a second precursor with a Dv50 particle size of 8 μm.

[0171] S3. Preparation of the third precursor:

[0172] Silicon deposition: The atmosphere was switched to a silane mixture (20% silane and 80% argon by mass), and the deposition was carried out at 0.1 MPa and 500 °C for 1 h. The silane flow rate was 0.5 L kg -1 min -1 , the deposition time is 20 minutes, and the third precursor is obtained.

[0173] S4, Carbon coating:

[0174] The third precursor is chemically vapor deposited by acetylene, and carbon is coated on the surface of the second precursor to obtain the final silicon-carbon material; the acetylene ventilation volume is 2 L·kg -1 min -1 , time is 480 min, temperature is 550℃.

[0175] Embodiment 2-4

[0176] The difference from Example 1 is that the amounts of ferrous sulfate and ferric chloride used in step S1 are changed according to Table 1, and the other conditions remain the same as in Example 1.

[0177] Examples 5-10, 19-20 and 22

[0178] The difference from Example 1 is that the type and amount of the transition metal salt used in step S1 are changed according to Table 1, and the other conditions remain the same as in Example 1.

[0179] Embodiment 11

[0180] The difference from Example 4 is that only the pressure of silicon deposition in step S3 is changed to 200 kPa, and the other conditions remain the same as those in Example 4.

[0181] Example 12

[0182] The difference from Example 8 is that only the pressure of silicon deposition in step S3 is changed to 200 kPa, and the other conditions remain the same as in Example 8.

[0183] Embodiment 13

[0184] The difference from Example 4 is that only the type and ventilation volume of the gas source for silicon deposition in step S3 are changed. When a silane mixed gas (20% silane and 80% argon by mass percentage) is introduced, a carborane mixed gas (20% carborane and 80% argon by mass percentage) is introduced, wherein the silane ventilation volume is 0.5 L·kg -1 min -1 , the carborane ventilation volume is 0.01 L·kg -1 ·min -1 The remaining conditions remain the same as those in Example 4.

[0185] Embodiment 14

[0186] The difference from Example 8 is that only the type and ventilation volume of the gas source for silicon deposition in step S3 are changed. When a silane mixed gas (20% silane and 80% argon by mass percentage) is introduced, a carborane mixed gas (20% carborane and 80% argon by mass percentage) is introduced, wherein the silane ventilation volume is 0.5 L·kg -1 min -1 , the carborane ventilation volume is 0.01 L·kg -1 ·min -1 The remaining conditions remain the same as those in Example 8.

[0187] Embodiment 15

[0188] The difference from Example 4 is that only the type and ventilation volume of the gas source for silicon deposition in step S3 are changed. While the silane mixed gas (20% silane and 80% argon by mass percentage) is introduced, a gallium nitrate mixed gas (20% gallium nitrate and 80% argon by mass percentage) is introduced, wherein the silane ventilation volume is 0.5 L kg -1 min -1 , the gallium nitrate ventilation rate is 0.5 mg kg -1 ·min -1 The remaining conditions remain the same as those in Example 4.

[0189] Example 16

[0190] The difference from Example 8 is that only the type and ventilation volume of the gas source for silicon deposition in step S3 are changed. While the silane mixed gas (20% silane and 80% argon by mass percentage) is introduced, a gallium nitrate mixed gas (20% gallium nitrate and 80% argon by mass percentage) is introduced, wherein the silane ventilation volume is 0.5 L·kg -1 min -1 , the gallium nitrate ventilation rate is 0.5 mg kg -1 ·min -1 The remaining conditions remain the same as those in Example 8.

[0191] Embodiment 17

[0192] The difference from Example 4 is that only the type and ventilation volume of the gas source for silicon deposition in step S3 are changed. When a silane mixed gas (20% silane and 80% argon by mass percentage) is introduced, a phosphine mixed gas (20% phosphine and 80% argon by mass percentage) is introduced, wherein the silane ventilation volume is 0.5 L kg -1 min -1 , phosphine ventilation volume is 0.01L·kg -1 ·min -1 The remaining conditions remain the same as those in Example 4.

[0193] Embodiment 18

[0194] The difference from Example 8 is that only the type and ventilation volume of the gas source for silicon deposition in step S3 are changed. When a silane mixed gas (20% silane and 80% argon by mass percentage) is introduced, a phosphine mixed gas (20% phosphine and 80% argon by mass percentage) is introduced, wherein the ventilation volume of silane is 0.5 L·kg -1 min -1 , phosphine ventilation volume is 0.01L·kg -1 ·min -1 The remaining conditions remain the same as those in Example 8.

[0195] Embodiment 21

[0196] The difference from Example 4 is that in step S2, hydrogen reduction is not performed, and carbon deposition is performed directly. The other conditions are the same as those in Example 4.

[0197] Comparative Example 1

[0198] The porous carbon-loaded silicon substrate prepared in Example 1 was used as the negative electrode material.

[0199] Comparative Example 2

[0200] The difference from Example 4 is that step S3 is not performed, and the second precursor prepared in step S2 is directly used for carbon coating in step S4, and the other conditions are the same as those in Example 4.

[0201] Comparative Example 3

[0202] The difference from Example 4 is that no transition metal salt is added in step S1, and the other conditions are the same as those in Example 4.

[0203] The types and amounts of transition metal salts in the above Examples 1-22 and Comparative Examples 1-3 are shown in Table 1.

[0204]

[0205] Effect Example 1

[0206] The intermediate products and the final silicon-carbon materials in Examples 1-22 and Comparative Examples 1-3 were tested as follows:

[0207] (1) Dv50 particle size: tested using Masterizer-2000 laser particle size analyzer.

[0208] (2) The BET test and full-hole test were performed using Micromeritics' ASAP2020.

[0209] (3) Silicon and iron content: The silicon and iron content was measured using an inductively coupled plasma spectrometer (ICP, Agilent, model Agilent 5800).

[0210] (4) Carbon content: Use a high-frequency carbon-sulfur analyzer (model DK-606) to test the carbon content.

[0211] (5) Raman spectroscopy test (Raman): The ID / IG in the result is usually used to characterize the degree of disorder of the material. In the nano-silicon-carbon composite material, the higher the degree of disorder of the graphite-like layer, the stronger its buffering effect on the expansion of silicon-intercalated lithium. There are two characteristic peaks in the Raman spectrum curve, with the peak value located at 1310~1360cm -1 The peak between is the disorder peak (D peak); located at 1560~1610cm -1 The peak between the D peak and the G peak is the graphite peak (G peak). The integrated area ratio of the D peak to the G peak (ID / IG) can characterize the degree of disorder or graphitization of the material. The smaller the ID / IG, the lower the degree of disorder and the higher the degree of graphitization.

[0212] (6) 1MPa powder resistivity: A powder conductivity meter (model FT-8100) is used based on the four-probe test principle and the test standard is GB / T 1552-1995. 3g of the sample to be tested is compressed to a set pressure value or pressure (1MPa) under hydraulic power, and the resistivity of the sample to be tested is measured online.

[0213] (7) Single particle strength:

[0214] The test was carried out using Yuanneng Technology's single particle mechanical properties testing system SPFT2000.

[0215] Effect Example 2

[0216] Preparation of pole pieces and lithium-ion batteries

[0217] Preparation of negative electrode slurry and pole piece: The negative electrode formula is designed as CMC: PAA: SBR: SP: CNTs: silicon-carbon material: graphite = 1: 3: 1: 0.1: 0.1: 8: 86.8 (by mass ratio). The time flow of negative electrode slurry preparation is graphite → CMC → SP → CNTs. After that, it is dispersed for 3 hours with a planetary disperser at a rotation speed of 300 r / min and a revolution of 1000 r / min. Then, 80% of deionized water is injected at a time, and it is dispersed at a speed of 500 r / min and a revolution of 600 r / min for 1 hour. PAA is added and dispersed at a rotation speed of 500 r / min and a revolution of 500 r / min for 1 hour. 20% of deionized water is injected, and finally SBR is added and dispersed at a rotation speed of 300 r / min and a revolution of 300 r / min for 1 hour to obtain a negative electrode slurry (solid content is 40%). The coated current collector uses 8μm thick copper foil, coated on one side, with the coated side facing the negative electrode of the button battery, and the thickness of the active material coated on one side is 40μm, with a compaction density of 1.7g / cm 3 The coating speed is 40 cm / s, followed by drying at a temperature of 80°C for 400 seconds.

[0218] Electrolyte preparation: The electrolyte composition, by mass percentage, is: EC 10%, PC 15%, DEC 20%, PP 30%, LiPF6 15%, FEC 6%, PS2.5% and LiODFB 1.5%.

[0219] Half-cell preparation: The positive electrode uses the above single-piece negative electrode sheet, the negative electrode uses a lithium sheet, the electrolyte addition amount is 0.5mL, and it is assembled into a CR2450 button battery. The voltage serial port uses 0-1.5V. The entire battery is assembled in a glove box to avoid contact with air.

[0220] Pole performance test:

[0221] (1) Expansion of the first lithium insertion cycle: (thickness of the electrode after saturated lithium insertion - thickness of the copper foil) / (thickness of the electrode without lithium insertion - thickness of the copper foil) - 1.

[0222] (2) Compacted density: Punch the electrode into a unit circle, test the weight, subtract the weight of the copper foil, and divide by the thickness to obtain the compacted density.

[0223] Electrochemical performance test:

[0224] (1) First effect: First assemble a CR2450 button battery, then discharge it at a constant voltage of 0.1 V / h to 0.000 V, record the discharge capacity, charge it at 0.1 V / h to 1.5 V, record the charge capacity, and calculate the first effect by dividing the discharge capacity by the charge capacity.

[0225] (2) 0.1C 0.8V gram capacity (measured at 25℃ and 45℃ respectively, the test system used is Xinwei CT-4008Q-5V6A): First, assemble a CR2450 button cell. Then, discharge it at a constant voltage of 0.1V / h to 0.000V, then charge it at 0.1V / h to 0.8V, record the 0.1C current of the charging capacity, reassemble a CR2450 button cell, and perform a constant current charge and discharge test at a constant current of 0.1C to record the charging capacity. After discharging to 0V, charge it to 0.8V to obtain the capacity. The gram capacity of 0.1C 0.8V = capacity / mass of active material in the electrode. The mass of active material in the electrode = mass of silicon-carbon material + mass of graphite.

[0226] (3) 0.5C 0.8V cycle failure number (measured at 25℃ and 45℃ respectively): First, assemble a CR2450 button cell. Then, discharge it at a constant voltage of 0.1V / h to 0.000V. Then, charge it at a constant voltage of 0.1V / h to 0.8V. Record the 0.5C current of the charging capacity. Reassemble a CR2450 button cell. Perform a constant current charge and discharge test at a constant current of 0.5C to record the charging capacity. Repeat the charge and discharge test from 0V to 0.8V. Record the discharge capacity. Terminate the test when the discharge capacity is 60% of the 0.5C 0.8V capacity. Record the number of cycles.

[0227] (4) 1C 0.8V cycle failure number (measured at 25℃ and 45℃ respectively): First, assemble a CR2450 button cell. Then, discharge it at a constant voltage rate of 0.1V / h to 0.000V. Then, charge it at a rate of 0.1V / h to 0.8V and record the charge capacity. Reassemble a CR2450 button cell and perform a constant current charge and discharge test at a 1C current with the charge capacity recorded. Repeatedly charge and discharge from 0V to 0.8V and record the discharge capacity. The test is terminated when the discharge capacity is 60% of the 1C 0.8V capacity and the number of cycles is recorded.

[0228] (5) Rate retention and hot box cycle retention

[0229] Retention rate at different rates at 25℃ (%): At 25℃, 1C 0.8V cycle failure number / 0.5C 0.8V cycle failure number.

[0230] Retention rate at different rates at 45℃ (%): At 45℃, 1C 0.8V cycle failure number / 0.5C 0.8V cycle failure number.

[0231] Hot box cycle retention rate (%): 0.5C 0.8V cycle failure number at 45℃ / 0.5C 0.8V cycle failure number at 25℃.

[0232] The test results of Effect Examples 1 and 2 are shown in Tables 2 to 5.

[0233] As shown below, Table 2 shows the corresponding test parameters of the first precursor and the second precursor obtained in Examples 1-22 and Comparative Examples 1-3.

[0234] As shown below, Table 3 shows the corresponding test parameters of the third precursor obtained in Examples 1-22 and Comparative Examples 1-3.

[0235] As shown below, Table 4 shows the corresponding test parameters of the silicon-carbon materials obtained in Examples 1-22 and Comparative Examples 1-3.

[0236] As shown below, Table 5 shows the electrochemical performance characterization results of lithium-ion batteries obtained by using the silicon-carbon materials obtained in Examples 1-22 and Comparative Examples 1-3 as negative electrode materials.

[0237]

[0238]

[0239]

[0240]

[0241] Note: “ / ” in the above table means that the condition parameter is not involved in the specific experiment.

[0242] From the above results, it can be seen that the silicon-carbon material in Examples 1-22 of the present invention has excellent electrical conductivity and high compressive strength. Specifically, the 1MPa powder resistivity can be lower than 13.2 Ω·cm, or even lower than 3 Ω·cm, the single particle strength can reach more than 8MPa, or even more than 20MPa, and the ID / IG can be higher than 0.22. The lithium-ion battery prepared using the silicon-carbon material as the negative electrode material can have a 1C 0.8V cycle failure number of more than 1000 cycles at 25°C. On this basis, the first efficiency can reach more than 80%, the lithium insertion expansion of the pole piece can be less than 25%, and the 0.1C 0.8V gram capacity can reach more than 1560 mAh / g.

[0243] Compared with Example 1, in Comparative Example 1, only porous carbon was used to load the silicon matrix without further subsequent coating treatment. Although the ID / IG of the obtained silicon-carbon material was higher, the 1MPa powder resistivity was significantly increased and the single particle strength was significantly reduced. The number of 1C 0.8V cycle failures, 0.1C 0.8V gram capacity and first efficiency of the prepared lithium-ion battery at 25°C were significantly deteriorated, and the lithium insertion expansion of the pole piece was significantly increased.

[0244] Compared with Example 4, there is no step S3 in Comparative Example 2, that is, no silicon is deposited, and no silicon nanowires and / or silicon nanoparticles are formed in situ in the carbon nanotubes. Although the ID / IG and 1MPa powder resistivity of the obtained silicon-carbon material are comparable, the single particle strength is reduced. The number of 1C 0.8V cycle failures, 0.1C 0.8V gram capacity and first efficiency of the prepared lithium-ion battery at 25°C are all low, and the lithium insertion expansion of the pole piece is also poor.

[0245] Compared with Example 4, no transition metal salt was added in Comparative Example 3, and carbon nanotubes would not be grown in situ during the subsequent carbon deposition. Although the ID / IG of the obtained silicon-carbon material was high, the 1MPa powder resistivity and single particle strength were significantly poor. The prepared lithium-ion battery could not take into account the excellent 1C 0.8V cycle failure number at 25°C, 0.1C 0.8V gram capacity and first efficiency, and the lithium expansion of the pole piece was also poor.

[0246] The silicon-carbon materials obtained in Examples 1-5 have a larger specific surface area, a lower resistivity, and a smaller ID / IG, which means that they have a higher graphitization and a more uniform carbon nanotube distribution. This may be because when the transition metal salt is a divalent salt or a trivalent salt of iron, the carbon nanotubes tend to grow single-walled carbon nanotubes (the structural schematic diagrams of the obtained silicon-carbon materials are shown in FIG. Figure 2 as shown).

[0247] In Examples 6-10, when the transition metal salt is only a trivalent salt of iron, as the amount of the transition metal carbon nanotube catalyst increases, the growth of carbon nanotubes tends to grow multi-walled carbon nanotubes (the structural schematic diagrams of the obtained silicon-carbon materials are shown in FIG. Figure 1 as shown).

[0248] Figure 1 and Figure 2 The obtained silicon-carbon material includes a core and an outer shell, the core includes a porous carbon-loaded silicon matrix (including porous carbon 3 in the porous carbon-loaded silicon matrix and silicon particles 4 in the porous carbon-loaded silicon matrix), and along the direction away from the core, the outer shell includes a first carbon layer 6 and a second carbon layer 7 in sequence, at least one of the first carbon layer 6 and the second carbon layer 7 is distributed with carbon nanotubes 5, and at least part of the carbon nanotubes 5 is distributed with silicon nanoparticles 1 and / or silicon nanowires 2. Figure 1 and Figure 2 In the figure, the green balls in the porous carbon-supported silicon matrix represent the schematic locations of transition metal-based carbon nanotube catalysts (transition metal salts). Most of the transition metal salts will be washed away during the acid washing process.

[0249] Examples 11-12 are pressure controlled separately. It can be seen from Table 5 that, based on Example 4, the 0.1C 0.8V gram capacity and the number of 1C 0.8V cycle failures at 25°C of the lithium-ion battery prepared from the silicon-carbon material of Example 11 change slightly, while the corresponding parameters of Example 12 change more significantly than those of Example 8. This may be because the pressure control under the condition of constant deposition amount has a weaker effect on the deposition effect of silicon in single-walled carbon nanotubes, while a stronger effect on multi-walled carbon nanotubes. This is mainly because the pore size of single-walled carbon nanotubes is smaller, and its deposition and adsorption effect on gas is less affected by gas pressure than that of multi-walled carbon nanotubes, which leads to more obvious performance changes when silicon is deposited in multi-walled carbon nanotubes under high pressure.

[0250] Examples 13-18 are cases where doping is performed simultaneously during silicon deposition. As can be seen from Table 5, doping has a certain effect on the cycle of the obtained lithium-ion battery and the amount of lithium-insertion expansion of the pole piece. The main reasons for this may be: (1) heteroatom doping can make silicon particles disordered, thereby improving the strength of the carbon nanotube-silicon nanowire-doped element composite material; (2) heteroatom elements such as N and P doping cause defects, which improve the ability to conduct electrons, making the surface potential distribution of silicon-carbon materials more uniform when used as negative electrode materials, and improving the embedding and extraction speed of lithium ions on the surface of silicon-carbon materials; (3) heteroatom doping further improves the disorder of silicon and widens the ion channel, especially for gallium nitrate, in which gallium atoms can further enhance the above effects, and the lithium nitride generated during the first charge and discharge process can further enhance the ion conduction level. Doping with both N and gallium greatly reduces the transmission rate and improves the rate, which is better than the case of single doping.

[0251] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A method for preparing a silicon-carbon material, characterized in that: It includes the following steps: S1, adding an alkaline reagent to a mixed solution containing a porous carbon-supported silicon substrate, a transition metal salt and a solvent, and drying to obtain a first precursor; S2, performing carbon deposition on the first precursor by chemical vapor deposition to in-situ grow carbon nanotubes, and then acid-washing and drying to obtain a second precursor; S3, using chemical vapor deposition to deposit silicon on the second precursor, forming silicon nanoparticles and / or silicon nanowires in situ in the carbon nanotubes, to obtain a third precursor; wherein the gas source for the silicon deposition includes a silicon source; S4. Carbon-coating the third precursor to obtain the silicon-carbon material.

2. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S1, the transition metal salt includes one or more of an iron salt, a nickel salt and a cobalt salt; And / or, in step S1, the transition metal salt further comprises a divalent salt and / or a trivalent salt of a transition metal; Preferably, in step S1, the transition metal salt comprises a divalent salt and a trivalent salt of iron; wherein the molar ratio of the divalent salt and the trivalent salt of iron is preferably (2-4): 1; And / or, in step S1, the transition metal salt includes one or more of transition metal hydrochloride, transition metal nitrate, transition metal sulfate, transition metal acetate and transition metal citrate; Preferably, the transition metal salt includes ferrous sulfate and ferric chloride; Preferably, the transition metal salt includes cobaltous sulfate and cobalt chloride; Preferably, the transition metal salt comprises ferric chloride; Preferably, the transition metal salt comprises ferric nitrate; Preferably, the transition metal salt comprises cobalt nitrate; And / or, in step S1, the content of the transition metal salt is 0.01-0.3 mol / kg, for example, 0.02 mol / kg, and the content is the molar number of the transition metal element in the transition metal salt relative to 1 kg of the porous carbon-supported silicon substrate; And / or, in step S1, the alkaline reagent includes a weak base reagent and / or a strong base reagent, preferably ammonia water; The concentration of the ammonia water is preferably 1-10%, for example 5%, where the percentage is the mass of ammonia to the total mass of the ammonia water; And / or, in step S1, the mass ratio of the alkaline reagent to the solvent is (1-10): 100; And / or, in step S1, the mixed solution further comprises a complexing agent; Wherein, the complexing agent preferably includes an organic acid and / or an organic acid salt, more preferably includes one or more of acetic acid, citric acid, EDTA and salts thereof, for example, includes one or more of ferric acetate, sodium acetate, ferric citrate, sodium citrate and EDTA; Wherein, the mass ratio of the complexing agent to the porous carbon-supported silicon substrate is preferably 1:(5-1000), for example 1:10; And / or, in step S1, the solvent is deionized water; And / or, in step S1, the mass ratio of the porous carbon-supported silicon substrate to the solvent is 1:(5-50), for example, 1:

10.

3. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S1, the alkaline reagent is added dropwise, and the dropping speed of the alkaline reagent is 5-50 mL / min, for example, 10 mL / min; And / or, in step S1, the adding is performed under stirring conditions; Wherein, the stirring speed is preferably 100-1000r / min, for example 300r / min; And / or, in step S1, the operation of adding the alkaline reagent is performed under a protective atmosphere; the protective atmosphere preferably includes one or more of an inert atmosphere, a reducing atmosphere and a carbon dioxide atmosphere, for example, includes one or more of nitrogen, argon, helium, hydrogen and carbon monoxide; And / or, in step S1, the method for preparing the mixed solution comprises: immersing the porous carbon-supported silicon substrate in a solvent, and then adding a transition metal salt to obtain a mixed solution; And / or, in step S1, after adding the alkaline reagent and before drying, an alcoholization step is further included; the alcoholization temperature is preferably 80-100° C., such as 90° C.; the alcoholization time is preferably 1-10 h, such as 5 h; And / or, in step S1, the drying satisfies one or more of the following conditions ①-④: ① The drying is spray drying; ② The drying speed is 0.5-3kg / h, for example 1kg / h; ③ The drying temperature is 150-300°C, for example 200°C; ④ The drying is carried out under a protective atmosphere, such as nitrogen; And / or, in step S1, the Dv50 particle size of the first precursor is 1-10 μm, for example, 8 μm.

4. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S1, the method for preparing the porous carbon-supported silicon substrate comprises: depositing silicon on porous carbon using a chemical vapor method to obtain a porous carbon-supported silicon substrate; Preferably, the silicon deposition satisfies one or more of the following conditions ①-③: ① The gas source for silicon deposition includes a silicon source, and the silicon source includes silane, and the silane preferably includes one or more of monosilane, disilane, trisilane and butasilane; Wherein, the gas source for silicon deposition preferably includes a silicon source and a carrier gas; wherein the volume ratio of the silicon source to the carrier gas is preferably 1:(2-6), for example, 1:4; ② The temperature of silicon deposition is 400-800° C., for example, 500° C.; ③ The silicon deposition time is 1-20 hours, for example, 10 hours; Preferably, the step of coating a passivation layer is further included after the silicon deposition; the passivation layer preferably includes a carbon layer and / or an oxide layer; preferably, the carbon layer is obtained by carbon deposition using a chemical vapor deposition method; Wherein, the gas source for carbon deposition includes a carbon source, and the carbon source preferably includes one or more of alkynes, alkanes, alkenes, aromatic compounds and carbohydrates; preferably, the gas source for carbon deposition includes a carbon source and a protective gas, and the protective gas preferably includes one or more of nitrogen, helium and argon; In the process of carbon deposition, the ventilation volume of the carbon source is preferably 0.1-10 L·kg -1 ·min -1 , for example 5L·kg -1 ·min -1 ; Wherein, the carbon deposition time is preferably 2-20h; The carbon deposition temperature is preferably 400-800°C, such as 500°C.

5. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S2, the carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes; wherein the pore size of the multi-walled carbon nanotubes is preferably 5-50 nm; and the pore size of the single-walled carbon nanotubes is preferably 2-20 nm; And / or, in step S2, before the carbon deposition, the step of reducing the first precursor is also included; Wherein, the reduction temperature is preferably 400-800°C, for example 550°C; The reduction is preferably carried out in a reducing atmosphere; the reducing atmosphere is preferably hydrogen; the ventilation volume of the reducing atmosphere is preferably 0.1-10 L·kg -1 ·min -1 , for example 1L kg -1 ·min -1 ; Wherein, the reduction time is preferably 30-300 min, for example 120 min; and / or, in step S2, the carbon source of the carbon deposition includes one or more of alkynes, alkanes, olefins, aromatic compounds and carbohydrates; And / or, in step S2, during the carbon deposition process, the ventilation volume of the carbon source is 2-10 L·kg -1 ·min -1 ; And / or, in step S2, the carbon deposition time is 5-120 min, for example, 15 min; and / or, in step S2, the temperature of the carbon deposition is 500-700°C, for example, 550°C; And / or, the pickling comprises a step of washing with hydrochloric acid; the mass ratio of the hydrochloric acid to the product obtained by the carbon deposition is (5-50):1, for example, 10:1; preferably, the concentration of the hydrochloric acid is 1-6 mol / L; And / or, the drying method is spray drying or vacuum drying; And / or, in step S2, the Dv50 particle size of the second precursor is 4-20 μm, for example, 8 μm.

6. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S3, when the silicon is deposited, silicon nanowires are formed in situ in the multi-walled carbon nanotubes; silicon nanoparticles are formed in situ in the single-walled carbon nanotubes; And / or, in step S3, the temperature of silicon deposition is 400-800° C., for example, 500° C.; And / or, in step S3, the silicon deposition time is 5-60 min, for example, 20 min; And / or, in step S3, the silicon source comprises silane, and the silane preferably comprises one or more of monosilane, disilane, trisilane and butasilane; And / or, in step S3, the ventilation volume of the silicon source is 0.01-1 L·kg -1 min -1 , for example 0.5 L·kg -1 min -1 ; and / or, in step S3, the silicon deposition is performed at a pressure of 0.1-2 MPa, for example, at 0.2 MPa; And / or, in step S3, the gas source for silicon deposition further includes a carrier gas; wherein the volume ratio of the silicon source to the carrier gas is 1:(2-6), for example, 1:4; And / or, in step S3, the gas source for silicon deposition further comprises a doping element gas, and the doping element gas preferably comprises one or more of a Group III element compound gas and a Group V element compound gas, for example, one or more of carborane, gallium nitrate, phosphine and arsine; preferably, the amount of the doping element gas introduced is 0.01-0.5 L·kg -1 min -1 ; And / or, in step S4, the carbon coating comprises the following steps: performing carbon deposition on the third precursor by chemical vapor deposition; Wherein, the carbon source of the carbon deposition preferably includes one or more of alkynes, alkanes, olefins, aromatic compounds and carbohydrates; In the process of carbon deposition, the ventilation volume of the carbon source is preferably 0.1-10 L·kg -1 ·min -1 , for example 2L·kg -1 ·min -1 ; Wherein, the carbon deposition time is preferably 300-600 min, for example 480 min; The carbon deposition temperature is preferably 400-800°C, such as 550°C.

7. A silicon-carbon material, characterized in that: The silicon-carbon material is prepared by the method for preparing the silicon-carbon material according to any one of claims 1 to 6.

8. A silicon-carbon material, characterized in that: The silicon-carbon material includes a core-shell structure, which includes an inner core and an outer shell covering the inner core, wherein the inner core includes a porous carbon-loaded silicon matrix, and the outer shell includes a first carbon layer and a second carbon layer in sequence along a direction away from the inner core; wherein carbon nanotubes are distributed in at least one of the porous carbon-loaded silicon matrix, the first carbon layer and the second carbon layer, and silicon nanoparticles and / or silicon nanowires are distributed in at least some of the carbon nanotubes.

9. The silicon-carbon material according to claim 8, characterized in that: The distribution of the carbon nanotubes includes one or more of the following methods ①-⑤: ① The carbon nanotubes are distributed inside the porous carbon-supported silicon substrate; ② The carbon nanotubes extend from the interior of the porous carbon-loaded silicon substrate and sequentially penetrate the first carbon layer and the second carbon layer; ③ The carbon nanotubes extend from the interior of the porous carbon-loaded silicon substrate and penetrate the first carbon layer and are embedded in the second carbon layer; ④ The carbon nanotubes extend from the inside of the first carbon layer and penetrate the second carbon layer; ⑤ The carbon nanotubes extend from the inside of the first carbon layer and are embedded in the second carbon layer; And / or, the shell further comprises a silicon layer, wherein the silicon layer is located between the first carbon layer and the second carbon layer; and / or, the silicon nanoparticles and / or silicon nanowires include doping elements; The doping element preferably includes one or more of the third main group elements and the fifth main group elements, such as one or more of nitrogen, boron, gallium, phosphorus and arsenic; Wherein, the content of the doping element is preferably 0.05%-0.2%, for example, 0.1%; And / or, the silicon-carbon material satisfies one or more of the following conditions ①-⑨: ① The carbon content of the silicon-carbon material is 20%-80%, preferably 50%-60%; ② The silicon content of the silicon-carbon material is 20%-60%, preferably 40%-50%; ③ The iron content of the silicon-carbon material is 0.05%-0.1%; ④The nickel content of the silicon-carbon material is 0.05%-0.1%; ⑤ The cobalt content of the silicon-carbon material is 0.05%-0.1%; ⑥ The 1MPa powder resistivity of the silicon-carbon material is 0.01-20 Ω·cm, preferably 1-15Ω·cm; ⑦ The single particle strength of the silicon-carbon material is 5-30 MPa; ⑧The specific surface area of ​​the silicon-carbon material is 1-2 m 2 / g; ⑨ The Dv50 particle size of the silicon-carbon material is 5-10 μm, preferably 8-9.5 μm.

10. A lithium ion battery, characterized in that: It comprises the silicon-carbon material as described in any one of claims 7-9.

Citation Information

Cited By

  • Silicon-carbon-based composite material, preparation method thereof and application of silicon-carbon-based composite material in lithium ion battery

    CN120518058A

  • Silicon-carbon negative electrode material and preparation method and application thereof

    CN120878827A

  • Silicon-carbon negative electrode material, preparation method and application thereof

    CN120878827B

  • Silicon carbon material, preparation method thereof, negative electrode and battery

    CN121215767A

  • Method for improving structural stability of silicon carbon material

    CN122126853A